KUALITAS KANTOR AKUNTAN PUBLIK MEMODERASI PENGARUH PROBABILITAS KEBANGKRUTAN TERHADAP AUDIT DELAY - Santosa, Wahyu Iko; Dwirandra, AANB (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of  probability of bankruptcy and KAP quality audit delay and to test the variable quality of the firm as a moderating influence the probability of bankruptcy to audit delay. This study uses quantitative and qualitative data sourced on secondary data collected by observation method nonparticipant. The object of this research is manufacturing companies listed on the Stock Exchange in 2011-2014. Used sample of 320 companies after the purposive sampling. This research has been qualified with classic assumption test the feasibility of a model with coefficient of determination of 89.9%. Data analysis technique used is Moderate Regression Analysis. Based on the results of analysis show the probability of bankruptcy and quality KAP positive and significant impact on audit delay. The study also found that the quality of KAP able to moderate (strengthen) the effect of probability of bankruptcy to audit delay.
Keywords: Probability of Bankruptcy, KAP Quality, Audit Delay